2020
DOI: 10.3390/ijms21031072
|View full text |Cite
|
Sign up to set email alerts
|

CB1 Activity Drives the Selection of Navigational Strategies: A Behavioral and c-Fos Immunoreactivity Study

Abstract: To promote efficient explorative behaviors, subjects adaptively select spatial navigational strategies based on landmarks or a cognitive map. The hippocampus works alone or in conjunction with the dorsal striatum, both representing the neuronal underpinnings of the navigational strategies organized on the basis of different systems of spatial coordinate integration. The high expression of cannabinoid type 1 (CB1) receptors in structures related to spatial learning—such as the hippocampus, dorsal striatum and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 87 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…In other words, CS can serve as a motivating factor to initiate active responses that reduce exposure to the fear arousing stimulus. There is compelling evidence that the striatum and other regions of the basal ganglia play a role in learning how to select actions that result in rewarding outcomes (Laricchiuta et al, 2020) as well as in instrumental responses to avoid aversive stimuli (Wendler et al, 2013).…”
Section: Neural Bases Of Fcmentioning
confidence: 99%
“…In other words, CS can serve as a motivating factor to initiate active responses that reduce exposure to the fear arousing stimulus. There is compelling evidence that the striatum and other regions of the basal ganglia play a role in learning how to select actions that result in rewarding outcomes (Laricchiuta et al, 2020) as well as in instrumental responses to avoid aversive stimuli (Wendler et al, 2013).…”
Section: Neural Bases Of Fcmentioning
confidence: 99%
“…As is known to all, FOS is a proto-oncogene, which plays an important role in the process of life metabolism. 10,11 It has been reported that overexpression of FOS can induce cell apoptosis. 12,13 However, it is still unclear whether FOS knockdown can cause keratinocytes proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…The authors demonstrated that treatment with the CB1 antagonist, AM251, impaired spatial learning and modified the pattern of performed navigational strategies in a mouse model of Gaucher disease. The strength of the synaptic plasticity on the behavioral output is modulated by CB1 receptors, which leads to spatial navigational strategies [ 5 ].…”
mentioning
confidence: 99%